Evaluation of endothelial biomarkers as predictors of organ failures in septic shock patients. Issue 2 (June 2015) - Palud, Aurore; Parmentier-Decrucq, Erika; Pastre, Jean; De Freitas Caires, Nathalie; Lassalle, Philippe; Mathieu, Daniel
Highlights: Angiotensin-2 level is associated with the clinical severity of the septic injury. Angiotensin-2 level is associated with the clinical outcome of the septic injury. In patients with septic shock, endocan level is higher than in controls. If paradoxically low, endocan predicts the occurrence of a respiratory failure. Abstract: Background: Endothelial injury is recognized to trigger organ failures during the first 48 h of septic shock. We evaluate endothelial biomarkers at ICU admission in their ability to predict severity, outcome, and organ failures in septic shock patients. Methods: This prospective observational pilot study was conducted in a medical intensive care unit of a university hospital. Plasma levels of endothelial biomarkers as angiopoietin-2, sE-selectin or endocan were measured at ICU admission of 20 patients presenting with septic shock. Clinical and biological data were recorded at inclusion and each day during the first week. Results: Significant correlations were found between angiopoietin-2 and severity scores at Day 1: SAPS2 ( r 2  = 0.620; p  = 0.004) and LOD score ( r 2  = 0.681; p  = 0.001). The angiopoietin-2 level was significantly higher in patients presenting with organ failure such as hemodynamic, renal or hepatic failure. It correlated with catecholamine infusion dose and was higher in non survivors compared with survivors (33.5 [28.9–51.4] vs. 12.4 [6.4–14.7] ng/ml; p  = 0.001). In contrast, in that population presenting with septic shock, endocan level at inclusion was not related to any organ failure at inclusion or Day 1 but appeared lower in patients presenting with respiratory failure at Day 3 compared to those who do not (1.9 [0.99–3.1] vs 5.2 [3.1–17.2] ng/ml; p  = 0.032). The endocan level at inclusion was correlated with the decrease in PaO2 /FiO2 ratio at Day 2 ( r 2  = 0.628; p  = 0.0004) and Day 3 ( r 2  = 0.645; p  = 0.005). Endocan level <2.54 ng/ml at admission is predictive of a respiratory failure presence at Day 3. Conclusion: In septic shock patients, angiopoietine-2 is related with clinical severity during the first 24 h but only endocan is able to predict the presence of respiratory failure at Day 3.